Tuskulėnai Mass Burial Grounds Occurence: 1944 or 1945? - Černius, Remigijus (Genocidas ir rezistencija, 2017)
The purpose of this article is to establish the date when Soviet secret police agencies started to use the territory of Tuskulėnai Manor as mass burial grounds in Vilnius. The remains of people executed at the inner prison of the NKGB (MGB) of Lithuanian Soviet Socialist Republic were buried there. At the same time, another question had to be answered: who choose this place, Tuskulėnai Manor, as a location suitable for mass graves. Historiographical sources frequently apply a simplified scheme, stating that the territory of Tuskulėnai Manor started to be used as mass burial grounds from the date when at the inner prison of the NKGB of Lithuanian Soviet Socialist Republic death penalties started to be carried out, i.e., from the 28th September 1944. Still, when analysing more closely the data of archeologic excavations 1994-1996 in the territory of Tuskulėnai Manor, as well as reports of 2003 and NKGB (MGB) documents, some doubts occur whether there could be remains of 45 people buried that had been executed at secret police inner prison in September –December of the year 1944. Statistical analysis allows us to think than in autumn and winter of 1944, the territory of Tuskulėnai Manor had not been used for mass graves. NKGB (MGB) officers could bury the remains of the executed people employing other ways that had not been new for them: in single graves in the woods in Vilnius neighbourhood or in old cemeteries. Such methods were applied by the Soviet secret police agencies from the year 1950. Historiographical sources claim that the territory of Tuskulėnai Manor had been chosen for mass graves by Ivan Tkachenko, a lieutenant general, who had been appointed an authorized person by NKGB and NKVD of the USSR for Lithuanian Soviet Socialist Republic. This fact is confirmed in the documents of the Soviet secret police institutions. Still, there is no exact date of choosing this location indicated in these documents. I. Tkachenko, to coordinate activity of the repressive structures as an authorized person to Lithuanian Soviet Socialist Republic was appointed on 14th December 1944, while execution of prisoners at the inner prison of NKGB of Lithuanian Soviet Socialist Republic started on 28th September 1944. Such a chronological mismatch suggests that I. Tkachenko selected the territory of Tuskulėnai Manor for mass graves at the end of 1944 or at the beginning of 1945. New documents found in the archives confirm that Tuskulėnai Manor was handed over to the NKGB of Lithuanian Soviet Socialist Republic in January of 1945. Therefore, it can be stated, that the remains of people executed in the inner prison of the NKGB of Lithuanian Soviet Socialist Republic, first had been buried in the territory of Tuskulėnai Manor in January of 1945, while before that date, the Soviet secret police agencies applied different methods.